2007
DOI: 10.1016/j.biopsych.2006.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic Changes in Ventral Midbrain Dopaminergic Neurons Resulting from (+/−) -3,4-Methylenedioxymethamphetamine (MDMA—“Ecstasy”)

Abstract: Background: Although dopamine (DA) has been implicated in the psychostimulant properties of 3,4-methylenedioxymethamphetamine (MDMA), there is no detailed information on its modalities of action on single ventral midbrain dopaminergic neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Several studies have reported a crosstalk between serotonin and GABA system. Thus, the serotonin releaser MDMA depressed the inhibitory postsynaptic potential of GABAB receptor by activating of 5-HT1B receptor (Federici et al, 2007), and increased GABA efflux in the ventral tegmental brain area (Bankson and Yamamoto, 2004), which correlates with our behavioral data.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have reported a crosstalk between serotonin and GABA system. Thus, the serotonin releaser MDMA depressed the inhibitory postsynaptic potential of GABAB receptor by activating of 5-HT1B receptor (Federici et al, 2007), and increased GABA efflux in the ventral tegmental brain area (Bankson and Yamamoto, 2004), which correlates with our behavioral data.…”
Section: Discussionsupporting
confidence: 87%
“…A low dose of MDMA induce a 5-HT 2B receptor-dependent 5-HT release that most likely promotes subsequent DA release in NAcc, while a “high” dose activates also a 5-HT 2B receptor-/5-HT-independent DA release, probably via a direct effect of MDMA on DAT. In this regard, a recent study showed that, according to the dose, MDMA has a dual effect (5-HT dependent or independent) on DA neurons firing [46]. Although some literature supports these observations (i.e., the released 5-HT drives the release of DA), other data showed that fenfluramine, a selective 5-HT releaser, fails to induce DA release [47].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by additional observations that suggest serotonergic and dopaminergic systems inhibit NP‐Y (Guy & Pelletier 1988; Pelletier & Simard 1991; Dube et al . 1992) and that serotonin and dopamine are increased in response to METH and MDMA exposure (Samanin & Garattini 1993; Federici et al . 2007).…”
Section: Discussionmentioning
confidence: 99%
“…2002). Considering this, GH levels may be more directly linked to dopamine levels, as studies have shown dopamine increases following exposure to MDMA and METH (Samanin & Garattini 1993; Federici et al . 2007).…”
Section: Discussionmentioning
confidence: 99%